Management practices shape soil fungal diversity and functional traits in Swiss forests - Xingguo Han; Fabienne Kuhn; Flurin Leugger; Thibault Lachat; Nicolas Roth; Martin M. Gossner; Loïc Pellissier; Aline Frossard (European Journal of Soil Biology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Remdesivir is active in vitro against tick-borne encephalitis virus and selects for resistance mutations in the viral RNA-dependent RNA polymerase - Kristina Nyström; Edward Trybala; Joanna Said; Anette Roth; Marianela Patzi Churqui; Ambjörn Kärmander; Tomas Cihlar; John P. Bilello; Tomas Bergström; Martin Lagging (Infectious Diseases, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Click beetles (Elateridae) identify conservation units in Oriental and European beech forests - Giorgi Mamadashvili; Andrea Jarzabek-Müller; Hazan Alkan Akinci; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Diedus; Lars Drössler; Jamshid Eslamdoust; Kostadin B. Georgiev; Tigran Ghrejyan; et al. (Journal of Insect Conservation, 2025)
Beech trees form major parts of lowland temperate forests in the Western Palearctic. To protect biodiversity, many beech forests have been designated as World Heritage Sites or established as networks of beech forest reserves. However, the insect communities within these protected forests have not been well explored. In this study, elaterids (Elateridae, Coleoptera) in 26 beech forests, from France in the west to Iran in the east, were sample to identify conservation clusters and hotspots of biodiversity. Sampling was mostly carried out using window traps and all specimens were identified to the species level. A total of 118 species were identified including one previously unreported species. Community composition analyses that focused on rare species identified five clusters comprising distinct communities: (i) the Hyrcanian Forest in Iran, (ii) the Lesser Caucasus in Türkiye, Georgia and Armenia, (iii) the Greater Caucasus in Georgia, (iv) the Pyrenees and (v) a cluster made up of forests from Central Europe, the Balkan region and the Carpathians. After controlling for sampling effort (individuals), the highest richness was found in the Caucasus region. The proportion of endemics was highest in the Oriental beech forests of the Caucasus and in Hyrcanian forests. These findings highlight the unique biodiversity of beech forests and support calls for intensified conservation actions in beech forests, particularly in the Caucasus and Hyrcanian regions, which should be prioritized for conservation efforts, due to their unique fauna. Implications for insect conservation Our study underscores the importance of protecting beech forests, especially in the Caucasus and Hyrcanian regions, as they host unique and endemic insect species critical for biodiversity conservation.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

The fog harvesting Namib Desert dune grass Stipagrostis sabulicola promotes niche building by modifying substrate and atmosphere conditions - Martin Ebner; Anita Roth-Nebelsick; Hervé Bocherens; Felix Gschwender; Moritz Baumeister; Nashara Miranda Ebner; Karin Hohberg; Huei Ying Gan; Clemént Schneider; Gillian Maggs-Kölling; Eugene Marais; Ricarda Lehmitz; et al. (Journal of Arid Environments, 2025)

Exploring weight-related self-monitoring as a potential risk factor for eating disorder symptoms in adults – A systematic review and meta-analysis - Annika M. Roth; Judith R. Gruber; Andreas Reif; Martin Schultze; Silke Matura (Appetite, 2024)

Investigation of submarine groundwater discharge into the Baltic Sea through varved glacial clays - Nai-Chen Chen; Matt O'Regan; Wei-Li Hong; Thomas Andrén; Valentí Rodellas; Florian Roth; Carl-Magnus Mörth; Carl Regnéll; Hanna Sofia Marxen; Sophie ten Hietbrink; Tzu-Hao Huang; Richard Gyllencreautz; et al. (Continental Shelf Research, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Geographic distribution of the Cross Seamount beaked whale based on acoustic detections - Jennifer L. K. McCullough; E. Elizabeth Henderson; Jennifer S. Trickey; Jay Barlow; Simone Baumann‐Pickering; Roanne Manzano‐Roth; Gabriela Alongi; Stephen Martin; Selene Fregosi; David K. Mellinger; Holger Klinck; Angela R. Szesciorka; et al. (Marine Mammal Science, 2024)
Beaked whales produce frequency‐modulated echolocation pulses that appear to be species‐specific, allowing passive acoustic monitoring to play a role in understanding spatio‐temporal patterns. The Cross Seamount beaked whale is known only from its unique echolocation signal (BWC) with no confirmed species identification. This beaked whale spans the Pacific Ocean from the Mariana Archipelago to Baja California, Mexico, south to the equator, but only as far north as latitude 29°N. Within these warm waters, 92% of BWC detections occurred at night, 6% during crepuscular periods, and only 2% during daylight hours. Detections of BWC signals on drifting recorders with a vertical hydrophone array at 150 m depth demonstrated that foraging often occurred shallow in the water column (

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Drivers of tree-related microhabitat profiles in European and Oriental beech forests - Giorgi Mamadashvili; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Deidus; Lars Drössler; Céline Emberger; Kostadin B. Georgiev; Tigran Ghrejyan; Martin M. Gossner; Ruslan Hleb; et al. (Biological Conservation, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Dive characteristics of Cross Seamount beaked whales from long‐term passive acoustic monitoring at the Pacific Missile Range Facility, Kauaʻi - Roanne Manzano‐Roth; E. Elizabeth Henderson; Gabriela C. Alongi; Cameron R. Martin; Stephen W. Martin; Brian Matsuyama (Marine Mammal Science, 2023)
Beaked whale foraging pulses were detected on the Pacific Missile Range Facility (PMRF) off Kauaʻi, Hawaiʻi, via long term passive acoustic monitoring. The unidentified pulses do not match foraging pulses of known species on the range but are similar to the unidentified beaked whale first detected at Cross Seamount, Hawaiʻi. Although there has not been a visual confirmation of the unidentified beaked whale species, analysis of data collected from 2007 to 2019 has identified beaked whale foraging dive characteristics from echolocation pulses. From the 13 years of data, the most distinct patterns were that all foraging dives occurred at night and the nighttime foraging dive rate was 0.11 group vocal periods (GVP) per hour, with most detections on shallow hydrophones (625–1,000 m deep) over steep bathymetric slopes. Data collected during U.S. Navy training events were used to compare dive behavior during mid‐frequency active sonar (MFAS) activity against baseline periods; it was determined that the whales reduced GVPs during sonar and these remained low for at least 3 days after the training events. These results are the first long‐term record of acoustic signals from the Cross Seamount beaked whale and provide important insights into their habitat use and occurrence patterns.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Side-of-Implantation Effect on Functional Asymmetry in the Auditory Cortex of Single-Sided Deaf Cochlear-Implant Users - Anna Weglage; Verena Müller; Natalie Layer; Khaled H. A. Abdel-Latif; Ruth Lang-Roth; Martin Walger; Pascale Sandmann (Brain Topography, 2022)
Cochlear implants (CIs) allow to restore the hearing function in profoundly deaf individuals. Due to the degradation of the stimulus by CI signal processing, implanted individuals with single-sided deafness (SSD) have the specific challenge that the input highly differs between their ears. The present study compared normal-hearing (NH) listeners (N = 10) and left- and right-ear implanted SSD CI users (N = 10 left, N = 9 right), to evaluate cortical speech processing between CI- and NH-ears and to explore for side-of-implantation effects. The participants performed a two-deviant oddball task, separately with the left and the right ear. Auditory event-related potentials (ERPs) in response to syllables were compared between proficient and non-proficient CI users, as well as between CI and NH ears. The effect of the side of implantation was analysed on the sensor and the source level. CI proficiency could be distinguished based on the ERP amplitudes of the N1 and the P3b. Moreover, syllable processing via the CI ear, when compared to the NH ear, resulted in attenuated and delayed ERPs. In addition, the left-ear implanted SSD CI users revealed an enhanced functional asymmetry in the auditory cortex than right-ear implanted SSD CI users, regardless of whether the syllables were perceived via the CI or the NH ear. Our findings reveal that speech-discrimination proficiency in SSD CI users can be assessed by N1 and P3b ERPs. The results contribute to a better understanding of the rehabilitation success in SSD CI users by showing that cortical speech processing in SSD CI users is affected by CI-related stimulus degradation and experience-related functional changes in the auditory cortex.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

From tree to architecture: how functional morphology of arborescence connects plant biology, evolution and physics - Anita Roth-Nebelsick; Tatiana Miranda; Martin Ebner; Wilfried Konrad; Christopher Traiser (Palaeobiodiversity and Palaeoenvironments, 2021)
Trees are the fundamental element of forest ecosystems, made possible by their mechanical qualities and their highly sophisticated conductive tissues. The evolution of trees, and thereby the evolution of forests, were ecologically transformative and affected climate and biogeochemical cycles fundamentally. Trees also offer a substantial amount of ecological niches for other organisms, such as epiphytes, creating a vast amount of habitats. During land plant evolution, a variety of different tree constructions evolved and their constructional principles are a subject of ongoing research. Understanding the “natural construction” of trees benefits strongly from methods and approaches from physics and engineering. Plant water transport is a good example for the ongoing demand for interdisciplinary efforts to unravel form-function relationships on vastly differing scales. Identification of the unique mechanism of water long-distance transport requires a solid basis of interfacial physics and thermodynamics. Studying tree functions by using theoretical approaches is, however, not a one-sided affair: The complex interrelationships between traits, functionality, trade-offs and phylogeny inspire engineers, physicists and architects until today.

Model for leisure boat activities and emissions – implementation for the Baltic Sea - Lasse Johansson; Erik Ytreberg; Jukka-Pekka Jalkanen; Erik Fridell; K. Martin Eriksson; Maria Lagerström; Ilja Maljutenko; Urmas Raudsepp; Vivian Fischer; Eva Roth (Ocean Science, 2020)
The activities and emissions from leisure boats in the Baltic Sea have been modeled in a comprehensive approach for the first time, using a new simulation model leisure Boat Emissions and Activities siMulator (BEAM). The model utilizes survey data to characterize the national leisure boat fleets. Leisure boats have been categorized based on their size, use and engine specifications, and for these subcategories emission factors for NOx, PM2.5, CO, non-methane volatile organic compounds (NMVOCs), and releases of copper (Cu) and zinc (Zn) from antifouling paints have been estimated according to literature values. The modeling approach also considers the temporal and spatial distribution of leisure boat activities, which are applied to each simulated leisure boat separately. According to our results the CO and NMVOC emissions from leisure boats, as well as Cu and Zn released from antifouling paints, are significant when compared against the emissions originating from registered commercial shipping in the Baltic Sea. CO emissions equal 70 % of the registered shipping emissions and NMVOC emissions equal 160 % when compared against the modeled results in the Baltic Sea in 2014. Modeled NOx and PM2.5 from the leisure boats are less significant compared to the registered shipping emissions. The emissions from leisure boats are concentrated in the summer months of June, July and August and are released in the vicinity of inhabited coastal areas. Given the large emission estimates for leisure boats, this commonly overlooked source of emissions should be further investigated in greater detail.

Comparing temperature data sources for use in species distribution models: From in‐situ logging to remote sensing - Jonas J. Lembrechts; Jonathan Lenoir; Nina Roth; Tarek Hattab; Ann Milbau; Sylvia Haider; Loïc Pellissier; Aníbal Pauchard; Amanda Ratier Backes; Romina D. Dimarco; Martin A. Nuñez; Juha Aalto; et al. (Global Ecology and Biogeography, 2019)
Aim Although species distribution models (SDMs) traditionally link species occurrences to free‐air temperature data at coarse spatio‐temporal resolution, the distribution of organisms might instead be driven by temperatures more proximal to their habitats. Several solutions are currently available, such as downscaled or interpolated coarse‐grained free‐air temperatures, satellite‐measured land surface temperatures (LST) or in‐situ‐measured soil temperatures. A comprehensive comparison of temperature data sources and their performance in SDMs is, however, currently lacking. Location Northern Scandinavia. Time period 1970–2017. Major taxa studied Higher plants. Methods We evaluated different sources of temperature data (WorldClim, CHELSA, MODIS, E‐OBS, topoclimate and soil temperature from miniature data loggers), differing in spatial resolution (from 1″ to 0.1°), measurement focus (free‐air, ground‐surface or soil temperature) and temporal extent (year‐long versus long‐term averages), and used them to fit SDMs for 50 plant species with different growth forms in a high‐latitudinal mountain region. Results Differences between these temperature data sources originating from measurement focus and temporal extent overshadow the effects of temporal climatic differences and spatio‐temporal resolution, with elevational lapse rates ranging from −0.6°C per 100 m for long‐term free‐air temperature data to −0.2°C per 100 m for in‐situ soil temperatures. Most importantly, we found that the performance of the temperature data in SDMs depended on the growth forms of species. The use of in‐situ soil temperatures improved the explanatory power of our SDMs ( R 2 on average +16%), especially for forbs and graminoids ( R 2 +24 and +21% on average, respectively) compared with the other data sources. Main conclusions We suggest that future studies using SDMs should use the temperature dataset that best reflects the ecology of the species, rather than automatically using coarse‐grained data from WorldClim or CHELSA.

Color preference and spatial distribution of glaphyrid beetles suggest a key role in the maintenance of the color polymorphism in the peacock anemone (Anemone pavonina, Ranunculaceae) in Northern Greece - Martin Streinzer; Nicolas Roth; Hannes F. Paulus; Johannes Spaethe (Journal of Comparative Physiology A, 2019)

Monotone trends in the distribution of climate extremes - Martin Roth; Geurt Jongbloed; Adri Buishand (Theoretical and Applied Climatology, 2019)

Growth dynamics of endemic Dracaena cinnabari Balf. f. of Socotra Island suggest essential elements for a conservation strategy - Petr Maděra; Hana Habrová; Martin Šenfeldr; Irena Kholová; Samuel Lvončík; Lenka Ehrenbergerová; Matěj Roth; Nadezhda Nadezhdina; Petr Němec; Jonathan Rosenthal; Jindřich Pavliš (Biologia, 2019)

The diversity of saproxylic insects (Coleoptera, Heteroptera) on four tree species of the Hyrcanian forest in Iran - Jörg Müller; Hassan Barimani Varandi; Mohammad Reza Babaii; Mohammad Ebrahim Farashiani; Khosro Sageb-Talebi; Frank Lange; Martin M. Gossner; Andrea Jarzabek-Müller; Nicolas Roth; Simon Thorn; Sebastian Seibold (Journal of Insect Conservation, 2018)

Integration of sudden death syndrome resistance loci in the soybean genome - Hao-Xun Chang; Mitchell G. Roth; Dechun Wang; Silvia R. Cianzio; David A. Lightfoot; Glen L. Hartman; Martin I. Chilvers (Theoretical and Applied Genetics, 2018)

A biological blueprint for the axons of superficial layer pyramidal cells in cat primary visual cortex - Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Synaptic connections formed by patchy projections of pyramidal cells in the superficial layers of cat visual cortex - German Koestinger; Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Phytoremediation using microbially mediated metal accumulation in Sorghum bicolor - René Phieler; Dirk Merten; Martin Roth; Georg Büchel; Erika Kothe (Environmental Science and Pollution Research, 2015)

Siderophore production by streptomycetes—stability and alteration of ferrihydroxamates in heavy metal-contaminated soil - Eileen Schütze; Engy Ahmed; Annekatrin Voit; Michael Klose; Matthias Greyer; Aleš Svatoš; Dirk Merten; Martin Roth; Sara J. M. Holmström; Erika Kothe (Environmental Science and Pollution Research, 2015)

Discrimination between random and non-random processes in early bacterial colonization on biomaterial surfaces: application of point pattern analysis - Daniel Siegismund; Anja Schroeter; Claudia Lüdecke; Andreas Undisz; Klaus D. Jandt; Martin Roth; Markus Rettenmayr; Stefan Schuster; Sebastian Germerodt (Biofouling, 2014)

Neonatal steroids induce a down-regulation of tenascin-C and elastin and cause a deceleration of the first phase and an acceleration of the second phase of lung alveolarization - Matthias Roth-Kleiner; Thomas M. Berger; Sandrine Gremlich; Stefan A. Tschanz; Sonja I. Mund; Martin Post; Marco Stampanoni; Johannes C. Schittny (Histochemistry and Cell Biology, 2014)

Spinocerebellar Ataxias Type 8, 12, and 17 and Dentatorubro-Pallidoluysian Atrophy in Czech Ataxic Patients - Zuzana Musova; Zdenek Sedlacek; Radim Mazanec; Jiri Klempir; Jan Roth; Pavlina Plevova; Martin Vyhnalek; Marta Kopeckova; Ludmila Apltova; Anna Krepelova; Alena Zumrova (The Cerebellum, 2013)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Novel screening cascade identifies MKK4 as key kinase regulating Tau phosphorylation at Ser422 - Fiona Grueninger; Bernd Bohrmann; Klaus Christensen; Martin Graf; Doris Roth; Christian Czech (Molecular and Cellular Biochemistry, 2011)

Nuclear and incommensurate magnetic structure of NaFeGe2O6 between 5 K and 298 K and new data on multiferroic NaFeSi2O6 - Günther J. Redhammer; Anatoliy Senyshyn; Martin Meven; Georg Roth; Sebastian Prinz; Astrid Pachler; Gerold Tippelt; Clemens Pietzonka; Werner Treutmann; Markus Hoelzel; Björn Pedersen; Georg Amthauer (Physics and Chemistry of Minerals, 2011)

A cell culture system for the induction of Mallory bodies: Mallory bodies and aggresomes represent different types of inclusion bodies - Kiyoko Hirano; Bruno Guhl; Jürgen Roth; Martin Ziak (Histochemistry and Cell Biology, 2009)

Protein quality control: the who’s who, the where’s and therapeutic escapes - Jürgen Roth; Gary Hin-Fai Yam; Jingyu Fan; Kiyoko Hirano; Katarina Gaplovska-Kysela; Valerie Le Fourn; Bruno Guhl; Roger Santimaria; Tania Torossi; Martin Ziak; Christian Zuber (Histochemistry and Cell Biology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Array CGH identifies distinct DNA copy number profiles of oncogenes and tumor suppressor genes in chromosomal- and microsatellite-unstable sporadic colorectal carcinomas - Silke Lassmann; Roland Weis; Frank Makowiec; Jasmine Roth; Mihai Danciu; Ulrich Hopt; Martin Werner (Journal of Molecular Medicine, 2007)

Changes in the decomposer community when converting spruce monocultures to mixed spruce/beech stands - Michael Elmer; Martin La France; Gisela Förster; Mechthild Roth (Plant and Soil, 2004)

Interactions of temperature and angiotensin II in paraventricular neurons of rats in vitro - Mathias Dewald; Hans A. Braun; Martin T. Huber; Detlev Zwingmann; Joachim Roth; Karlheinz Voigt (Pflügers Archiv - European Journal of Physiology, 2002)

The importance of trimming reactions on asparagine-linked oligosaccharides for protein quality control - Jürgen Roth; Christian Zuber; Bruno Guhl; Jing-yu Fan; Martin Ziak (Histochemistry and Cell Biology, 2002)

Expression of a mutant ER-retained polytope membrane protein in cultured rat hepatocytes results in Mallory body formation - Kiyoko Hirano; Jürgen Roth; Christian Zuber; Martin Ziak (Histochemistry and Cell Biology, 2002)

The role of tumor necrosis factor (TNF) in the febrile and metabolic responses of rats to intraperitoneal injection of a high dose of lipopolysaccharide - Birgit Töllner; Joachim Roth; Birgit Störr; Dave Martin; Karlheinz Voigt; Eugen Zeisberger (Pflügers Archiv - European Journal of Physiology, 2000)

Expression of oligo/polyα2,8-linked deaminoneuraminic acid and megalin during kidney development and maturation: mutually exclusive distribution with polyα2,8-linked N -acetylneuraminic acid of N-CAM - Martin Ziak; J. Roth (Histochemistry and Cell Biology, 1999)

Megalin in normal tissues and carcinoma cells carries oligo/poly α2,8 deaminoneuraminic acid as a unique posttranslational modification - Martin Ziak; Mirjam Meier; Jürgen Roth (Glycoconjugate Journal, 1999)

Unconventional antigen retrieval for carbohydrate and protein antigens - Bruno Guhl; Martin Ziak; J. Roth (Histochemistry and Cell Biology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)